2018
DOI: 10.3171/2017.8.jns17854
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome of motor deficits and neurological status in brainstem cavernous malformations based on preoperative diffusion tensor imaging: a prospective randomized clinical trial

Abstract: OBJECTIVE Surgical management of brainstem lesions is challenging due to the highly compact, eloquent anatomy of the brainstem. This study aimed to evaluate the safety and efficacy of preoperative diffusion tensor imaging (DTI) and diffusion tensor tractography (DTT) in brainstem cavernous malformations (CMs). METHODS A prospective randomized controlled clinical trial was performed by using stratified blocked randomization. The primary eligibility criterion of the study was being a surgical candidate for brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Magnetic Resonance Imaging MRI has been found to show a higher specificity to detect both symptomatic and asymptomatic lesions as well as cavernomas located in the posterior cranial fossa or the brainstem [27,28]. Based on the MRI images, cavernous angiomas can be classified into 4 types ( Table 2).…”
Section: Diagnosismentioning
confidence: 99%
“…Magnetic Resonance Imaging MRI has been found to show a higher specificity to detect both symptomatic and asymptomatic lesions as well as cavernomas located in the posterior cranial fossa or the brainstem [27,28]. Based on the MRI images, cavernous angiomas can be classified into 4 types ( Table 2).…”
Section: Diagnosismentioning
confidence: 99%
“…Additionally, it may have promising value for the prediction of postoperative neurological function. 12,15,19 However, as brainstem gliomas behave differently from cavernous malformations and their ability to infiltrate the normal brain may vary depending on their genetic characteristics, the role of DTI/DTT in brainstem glioma surgery merits investigation. In our study, the number of changes in the CSTs in the deviation, deformation, and interruption groups were very similar.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, white matter tracts are more frequently deviated rather than destroyed by the lesions in brainstem cavernous malformations. 10,12 This discrepancy could be explained by the invasive nature of gliomas and indicate that these critical fibers are more vulnerable to surgical manipulation during an operation, thus meriting significant protective efforts. Understanding the anatomical relationship between the tumor and tracts is helpful to determine the approach, and many studies have shown that DTI/DTT is a highly valuable tool in preoperative surgical planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,116 Some studies report tractography to be a valuable tool that has shaped the surgical strategy of intra-axial lesions profoundly. This includes approaches to the brainstem, 36,135,163,176,178,198,221,222,234 the insula, 58,179,182,291 the thalamus, 158,162,195,202 and the angular gyrus. 167…”
Section: Tractography In Neurosurgical Planningmentioning
confidence: 99%